ANALISIS KESALAHAN BERBAHASA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA INDONESIA DALAM PENULISAN MAKALAH - Anindya Rizqi Setia Wardhani; Teti Sobari; Dede Abdurrokhman (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Low language skills are one of the obstacles in the communication process due to language errors. So this study aims to describe: (1) the types of errors contained in the paper, such as disclosure errors and transfer errors. (2) several factors that cause language errors. (3) As well as efforts to minimize errors that occur. The research method used is descriptive qualitative which contains explanations or descriptions written in detail, with a sample of 5 types of papers made by students. The results of the observations made were as follows: First, in the papers written by students, several types of language errors were still found, including: error in disclosure and transfer errors. Second, language errors that occur in writing papers are caused by several factors such as the influence of the learning process being / has been studied, not being careful when writing, a person's lack of knowledge of a language, environmental influences, or habitual factors. Third, language errors that occur in writing papers can be overcome with various efforts, among others: by providing sufficient knowledge of the types of language errors, being encouraged to learn more about the vocabulary of certain languages, and to increase the accuracy when carrying out writing activities.